Fine‐scale habitat associations of Oklahoma's longspurs. Issue 6 (16th June 2022) - Muller, John A.; Ross, Jeremy D.
Abstract: Overwintering is a key demographic stage for migratory birds but remains poorly understood, especially among multiple declining grassland bird species. The non‐breeding ranges all 4 species of longspur (i.e., chestnut‐collared [ Calcarius ornatus ], Smith's [ C. pictus ], Lapland [ C. lapponicus ], thick‐billed [ Rhynchophanes mccownii ]) overlap in Oklahoma and the Texas Panhandle, USA, making this region ideal to study their wintering ecology. We evaluated the relationship between wintering longspur occurrence and fine‐scale habitat characteristics using a combination of standardized bird surveys and vegetation plot sampling. Our study encompassed large, representative tracts of 3 prairie ecosystems (i.e., shortgrass, mixed‐grass, and tallgrass prairies) that intersect within the Southern Great Plains, during winters of 2018–2019 and 2019–2020. Using randomization tests and classification trees, we characterized longspur habitats and compared these associations across the 3 prairie ecosystems. Fine‐scale winter habitats (horizontal structure, vertical structure, and species compositions) varied among all 4 longspur species, varied at very fine scales, and differed between grassland types. Our findings can be applied to the management of grasslands such as decreasing vegetation height in mixed‐grass prairies for chestnut‐collared longspurs or removing woody vegetation in shortgrass prairies for thick‐billed longspurs to help develop full‐life cycle conservation for longspurs, which have experienced population declines. Abstract : We described wintering habitat associations of the 4 species of longspur overwintering in the Southern Great Plains across 3 different prairie ecotypes. We found that longspurs each use different habitats, and that key habitat associations change for various species depending on prairie ecotype.